2018
DOI: 10.20897/awet/3963
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Treatment of Domestic Wastewater Using Multi Soil Layering (MSL) System

Abstract: Soil has been used for the treatment of wastewater from long time ago. Domestic wastewater treatment and disposal is the serious problem our country is facing nowadays. If not treated it further pollutes the rivers. In villages or rural areas where centralized wastewater treatment is not possible because of the scattered houses, a decentralized treatment unit needs to be installed. Multi Soil Layering system is such a decentralized treatment used for the treatment of domestic wastewater. The main objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…This indicates that the function of intra-granular and inter-granular pores of permeable layers play an important role. This condition is in line with the observations by Deshpande [12] who found that the best TSS elimination is achieved through the filtration process with permeable layers and soil mixture block layers. On average, silica sand could eliminate TSS well at the Q1 and Q2 discharges.…”
Section: Figure 6 Reactor Efficiency For the First Stage Of Processingsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the function of intra-granular and inter-granular pores of permeable layers play an important role. This condition is in line with the observations by Deshpande [12] who found that the best TSS elimination is achieved through the filtration process with permeable layers and soil mixture block layers. On average, silica sand could eliminate TSS well at the Q1 and Q2 discharges.…”
Section: Figure 6 Reactor Efficiency For the First Stage Of Processingsupporting
confidence: 92%
“…For the pH parameter, zeolite at Q2 had the highest average pH efficiency enhancement with 5.33%, followed by silica sand at Q1 with 4.01% and pumice at Q1 with 3.61%. Enhancement of pH was not uniform for both discharges; this is in line with the results of the study by Deshpande [12] who explained that the effluent reactor pH in general is not affected by the influent flow rate and the aerated or non-aerated condition of the MSL system.…”
Section: Figure 6 Reactor Efficiency For the First Stage Of Processingsupporting
confidence: 88%